New Social Policy Agendas for Europe and Asia : Challenges, Experience, and Lessons - Marshall, Katherine; Butzbach, Olivier (Washington, DC: World Bank, 2013)
The Asia-Europe Meeting (ASEM) is the informal dialogue, and cooperative process linking the 15 European Union member states with 10 Asian nations, and who financed the project that brought together the experience of social policy experts, in an effort to highlight imperative thinking on new social policies, following the East Asia Crises of 1997-98. This book is the outcome of such project, which focused on ideas and knowledge exchange, working to develop a series of papers, and seminars drawing together different disciplines, and topics across both East Asia and Europe. A wide range of issues is addressed, including social security reform, the links between macroeconomic and social policy, labor market policies, gender relations, and cross-border migration. While the information is drawn from European experience, it is applicable to East Asia and other regions, and will be of interest to Asian studies, scholars, and students, interested in social policy formation.